2021
DOI: 10.1177/00033197211012546
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uric Acid in the Acute Myocardial Infarction: A Narrative Review

Abstract: Increased serum uric acid (SUA) levels have been associated with various pathologic processes such as increased oxidative stress, inflammation, and endothelial dysfunction. Thus, it is not surprising that increased SUA is associated with various adverse outcomes including cardiovascular (CV) diseases. Recent epidemiological evidence suggests that increased SUA may be related to acute myocardial infarction (AMI). Accumulating data also showed that elevated UA has pathophysiological role in the development of AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“…Moreover, elevated extracellular urate concentration aggravates the urate flux into cells. These events cause the accumulation of intracellular urate that aggravates ROS production ( 56 , 57 ), mitochondrial damage ( 58 ), endoplasmic reticulum stress ( 59 ), and apoptosis ( 56 ). These cellular events cause telomere shortening alone or in an interactive manner; in turn, telomere shortening further aggravates cell stress, forming a closed loop ( 20 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated extracellular urate concentration aggravates the urate flux into cells. These events cause the accumulation of intracellular urate that aggravates ROS production ( 56 , 57 ), mitochondrial damage ( 58 ), endoplasmic reticulum stress ( 59 ), and apoptosis ( 56 ). These cellular events cause telomere shortening alone or in an interactive manner; in turn, telomere shortening further aggravates cell stress, forming a closed loop ( 20 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidant property of UA is more prominent in the extracellular space as it can scavenge oxygen radicals such as hydroxyl, peroxyl, and singlet oxygen radicals and provide beneficial production of cells and organs from external oxidative stress. On the other hand, the pro-oxidant property of UA is more prominent intracellularly as enhanced activity of XO is directly linked to increased UA levels inside the cells and XO is one of the main ROS producers [1]. Also, elevated UA levels lead to activation of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase via translocation of regulatory components from the cytoplasm to the cell membrane, thus, forming the active holoenzyme [17].…”
Section: The Paradox Of Oxidant Versus Anti-oxidant Propertiesmentioning
confidence: 99%
“…Although no consensus on the optimal range for SUA levels is present, SUA levels of <6.0 mg/dL in women and <7.0 g/dL in men have been widely accepted as the goal of treatment in hyperuricemia patients [1]. However, some studies showed an increased risk for hypertension, dyslipidemia, and CKD for patients with high SUA levels even in the normal range.…”
Section: The Target Level For Ua Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies underlined increased serum UA as an important pathogenic factor for not only gout but also CVD, including myocardial infarction, stroke, and heart failure ( 29 , 30 ). Several pathophysiologic mechanisms may be responsible for the relationship between elevated serum UA levels and cardiometabolic diseases, including the imbalance of pro-oxidant and anti-oxidant effects, vascular endothelial function, inflammation, and the activation of the renin–angiotensin–aldosterone system (RAAS) ( 31 33 ). Additionally, the UA-dependent mitochondrial oxidative stress can drive the inhibition of fatty acid oxidation and stimulation of lipogenesis, finally inducing the development of fatty liver ( 34 ).…”
Section: Discussionmentioning
confidence: 99%